ANALISIS PENGARUH LITERASI KEUANGAN DAN RISK TOLERANCE TERHADAP KEPUTUSAN INVESTASI (STUDI KASUS PADA KELOMPOK STUDI PASAR MODAL (KSPM) UNIVERSITAS MATARAM) - Laila Wardani; Iwan Kusmayadi; Desi Rahmawati (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2023)
The purpose of this study is to find out the effect of financial literacy and risk tolerance on investment decisions of members of the Mataram University Capital Market Study Group (KSPM). The type of research used in this study is associative research. The data collection method used is a census method using primary data collected directly from respondents using questionnaires. The population in this study is all members of the Mataram University Capital Market Study Group (KSPM). The sample in this study was determined by a saturated sampling technique in which all 42 members of the population were sampled. The data analysis method used is the Partial Least Square (PLS) technique using the SmartPLS Partial Least Square (PLS) software application. The analysis results show that: (1) financial literacy has a positive and significant effect on investment decisions, and (2) risk tolerance has a positive but insignificant effect on investment decisions.